Strategi Pengembangan Objek Wisata Kolam Renang Tirta Plamboyan Desa Talang Kering Kecamatan Air Napal Kabupaten Bengkulu Utara - Dita Winastia Putri; Siti Hanila; Andriyani Prawitasari (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
The Tirta Plamboyan swimming pool tourist attraction which is located in Talang Dry Village, Air Napal District, North Bengkulu Regency is very likely to be developed with adequate resources, but this tourist attraction is not widely known to the outside community and is still lacking in terms of existing facilities. Therefore, the author takes the title "Strategy for the Development of the Tirta Plamboyan Swimming Pool Tourism Object, Talang Dry Village, Air Napal District, North Bengkulu Regency" the aim is to be able to find out what kind of development strategy is suitable for the Tirta Plamboyan swimming pool tourist attraction. The purpose of this study was to determine the strategy of developing a tourism object for the Tirta Plamboyan swimming pool, Talang Dry Village, Air Napal District, North Bengkulu Regency with SWOT analysis. The method used is descriptive qualitative with data collection techniques distributing questionnaires to respondents. The analytical method used is SWOT, namely Strengths , Weaknesses , Opportunities and Threats . The results of this study indicate that the Tirta Plamboyan swimming pool tourism object, Talang Dry Village, Air Napal District, North Bengkulu Regency is in quadrant II position. This shows that the strategy used is a diversification strategy . In addition, the results of the SWOT diagram using the ST strategy explain that the Tirta Plamboyan swimming pool tourist attraction is can maintain a cheap swimming pool ticket price from others, keep the swimming pool clean and create comfort in the swimming pool area, and approach the public not to think badly about the Tirta Plamboyan swimming pool.